Hydrogels - compounded dermatological preparations - Bianka Jacyna; Bartosz Maciejewski; Małgorzata Sznitowska (Polish Pharmaceutical Society, 2020)
Hydrogels are a physicochemical system in which an aqueous phase is gelled with a certain gelling polymer. They can make a good alternative to conventional lipophilic or absorption ointment bases, especially if the medicine should be administered to mucosa, because the gelling polymers interact with a mucose what results in mucoadhesion. The use of a hydrogel is preferred to lipophilic ointments in severe inflammations, exudative wounds, acne, oily skin or when the application area on the skin is hairy. Hydrogels also provide a cooling sensation on the skin, when water evaporates and this process is endothermic. Hydrogels are relatively popular also in a compounding practice in other countries, such as USA, where various types of commercially-made hydrogel bases are available. Despite the fact that hydrogels are accepted by law as compounded dosage forms, in Poland they have not been prepared in pharmacies because neither such bases nor suitable polymers are formally registered excipients for drug compounding, and the registration procedure is similar to the one for drug products authorization. The article describes hydrogels as there are first such materials available for pharmacists who are involved in compounding practice. Three gel-forming polymers: methylcellulose, hypromellose and hydroxyethylcellulose and hydrogel bases dedicated for drug compounding are characterized. Several examples of preparations with various active substances are presented and methods of their preparations are proposed. A dermatological base, Celugel, composed of hydroxyethylcellulose and recently registered in Poland for pharmacy compounding is also presented. Special attention is given to methods of hydrogel preparation, depending on the solubility profile of a certain type of polymer. Stability of the compounded hydrogels is discussed, especially regarding microbiological quality and the presence of preservatives. The benefits of these formulations are indicated including a relatively low cost of the hydrogel bases resulting from a low content of the polymers.